PENGARUH LAMA PERENDAMAN EKSTRAK DAUN MAHONI (sWIETENIA MAHAGONI) UNTUK PENGOBATAN PARASIT ARGULUS SP. PADA BENIH IKAN MAS (CYPRINUS CARPIO) - Ramayanti, Ramayanti; Komariyah, Siti; Putriningtias, Andika Putriningtias (Jurnal Cakrawala Ilmiah, 2024)
This study aims to analyze the soaking time for mahogany leaf extract (Swietenia mahagoni) for the treatment of the parasite Argulus sp. on goldfish fry and to analyze how long Argulus sp. will die after soaking with mahogany leaf extract using a dose of 0.8 g/liter of water with a soaking time according to the treatment. This research used a completely randomized design (CRD) consisting of 4 treatments and 3 replications with different soaking times for mahogany leaf extract in each treatment, namely: P0 = No soaking (control), P1 = Soaking time 6 hours, P2 = Soaking time 12 hoursand P3 = Soaking time 12 hours. The results of this research showed that the best soaking time was treatment (P3), namely 24 hours, and the lowest was treatment (P0), namely without mahogany leaf extract soaking. The highest percentage of survival was in treatment (P3), namely 100%, and the lowest was in treatment (P0) at 33.33%. The water quality parameters were quite good for the test fish, the results of water qualitymeasurements in this study were temperature 25-28oC, pH 6-9 and dissolved oxygen 7-9.